Effect of Surface Concentration of Lu on Oxygen Permeation of Polycrystalline Alumina at High Temperatures. Issue 7 (10th April 2013) - Wada, Masashi; Matsudaira, Tsuneaki; Kato, Takeharu; Kitaoka, Satoshi; Chan, H.
<x xml:space="preserve">Abstract</x> The effect of Lu surface concentration on oxygen permeation in polycrystalline α‐alumina wafers was determined at 1773 K under limited oxygen potential gradients (Δ<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdg9" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2), where the two surfaces of the wafer were deliberately subjected to different oxygen partial pressures [<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdhv" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 (I) ≪ <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdtt" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 (II)]. When oxygen permeation occurred mainly by oxygen GB diffusion under a Δ<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmds8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 generated by a combination of low <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdwx" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 values, the Lu‐coating on the <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdvc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 (I) [<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdq5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 (II)] surface decreased [increased] the oxygen permeability constants. When Δ<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdpm" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 was the result of a combination of high <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdrq" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 values, where oxygen permeation proceeded mainly by aluminum GB diffusion, the oxygen permeability constants were decreased only by the Lu‐coating on the <inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdjd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 (I) surface. The analysis of mass transfer parameters, such as the chemical potentials, GB diffusion coefficients, and fluxes of aluminum and oxygen in the wafers, suggested that ambient oxygen molecules were effectively attracted toward Lu‐coated surfaces exposed to low‐<inline-graphic mimetype="image" xlink:href="ark:/27927/pgg271cmdkz" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />PO2 environments, leading to a change in oxygen permeability.